Evaluation of HER2/neu Expression in High-Grade Endometrial Carcinoma and Its Clinicopathological Correlation - Soheila Sarmadi; Narges Izadi-Mood; Nazanin Mansourzadeh; Dorna Motevalli (Iranian Society of Pathology, 2019)
Background & Objective: Endometrial carcinoma (EC) has been traditionally classified into two distinct categories of low-grade and high-grade. Type I (low grade) EC, which constitutes the majority of cases, is linked to estrogen-related molecular pathways. But type II (high-grade) EC accounts for 10-20% of cases and behaves in an aggressive way. Pathologic and biological features of type II EC have not been fully elucidated yet. Several investigations have demonstrated HER2/neu expression and amplification in type II EC, especially papillary serous carcinoma (PSC). This study assessed HER2/neu expression in high-grade EC as well as its association with other clinical and histopathological prognostic factors. Methods: In this cross-sectional study, we performed HER2/neu immunohistochemical (IHC) staining in 37 high-grade EC cases with histological diagnostic categories of PSC (n=23), clear cell carcinoma (CCC) (n=9), and carcinosarcoma with high-grade carcinomatous component (PSC, CCC, grade 3 endometrioid carcinoma, or unclassified high-grade adenocarcinoma) (n=5). All patients were followed for 2-9 years in order to evaluate their disease-free survival (DFS) and overall survival (OS) during study period (2005-2014). Result: HER2/neu IHC staining was positive in 12 patients (32.4%) including 8/23 (34.8%) PSC, 2/9 (22.2%) CCC, and 2/5 (40%) carcinosarcoma cases. There was no statistically significant difference between HER2/neu expression and DFS or OS of the patients (P>0.05). Conclusion: We observed that HER2/neu is expressed in one-third of high-grade ECs. This ancillary test is supportive in follow-up of patients with high-grade ECs.